A taxonomic review of the Gyrinidae (Coleoptera) in Korea - Lee, Dae-Hyun (Zookeys, 2015)
Abstract. A taxonomic review of Korean Gyrinidae is presented. Seven species [Dineutus orientalis (Modeer, 1776), Gyrinus gestroi Régimbart, 1883, Gyrinus japonicus Sharp, 1873, Gyrinus pullatus Zaitzev, 1908, Orectochilus punctipennis Sharp, 1884, Orectochilus Regimbarti Sharp, 1884 and Orectochilus villosus (Müller, 1776)] in three genera are recognized, one of which (Orectochilus punctipennis Sharp, 1884) is reported for the first time in Korea. We also found that Gyrinus curtus Motschulsky, 1866 previously recorded in Korea was an incorrect identification of Gyrinus pullatus Zaitzev, 1908. Habitus and SEM photographs, distribution maps, keys, and diagnoses of genera and species are provided.